Experimental research of ammonia escape in CO2 absorption using ammonia solution in wetted-wall column. (August 2016) - Ma, Shuangchen; Chen, Gongda; Gao, Ran; Wen, Jiaqi; Ma, Lan
Graphical abstract: Highlights: Based on two film theory, model for measuring mass transfer coefficients of ammonia escape was built. Mass transfer coefficients of ammonia escape in CO2 absorption using ammonia solution were obtained under different conditions. Effects of various conditions on mass transfer coefficients of ammonia escape and CO2 absorption were obtained and analyzed. This paper provided a special research for mass transfer coefficients of ammonia escape. Abstract: Ammonia solution has many advantages to be used for CO2 capture, while ammonia escape is a serious problem of this technology. Ammonia escape leads to absorbent loss and secondary pollution. At present, there were few relevant researches on ammonia escape coefficient. The mass transfer coefficient of ammonia escape in absorption was studied theoretically based on double film theory. The relationship between mass transfer coefficient and other variables in the absorption process is analyzed through experiments, mass transfer coefficient of ammonia escape was strongly influenced by temperature, CO2 partial pressure, gas flow rate, and L/G. Compared with previous researches, mass transfer coefficients under different conditions were obtained in this study. In the experiments, max value of mass transfer coefficient reached 0.00071 mol/(kPa × m 2 × s). This research result has a certain reference value for solving the problem of ammonia escape in CO2 capture using ammonia solution, as well as the development of this technology.